2000
DOI: 10.1103/physrevd.62.063001
|View full text |Cite
|
Sign up to set email alerts
|

Calculation methods for radio pulses from high energy showers

Abstract: We present an approximation for the numerical calculation ofČerenkov radio pulses in the Fraunhofer limit from very high energy showers in dense media.We compare it to full Montecarlo simulations in ice studying its range of applicability and show how it can be extended with a simple algorithm. The approximation reproduces well the angular distribution of the pulse around theČerenkov direction. An improved parameterization for the frequency spectrum in theČerenkov direction is given for phenomenolgical applica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
138
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 107 publications
(142 citation statements)
references
References 30 publications
2
138
0
2
Order By: Relevance
“…If electron neutrinos are detected, the showers that come out of charged current interactions will have a different character depending on y because the neutrino induced electromagnetic (hadronic) shower arising at the leptonic (hadronic) vertex carries a fraction 1 − y (y) of the neutrino energy. In particular it has been recently suggested that it may be possible to measure y by using the radio technique [5]. This tecnique relies of the detection of coherent radio pulses from the excess charge in the induced showers in a dense medium such as ice.…”
Section: Low X Physics and High Energy Neutrino Telescopesmentioning
confidence: 99%
See 2 more Smart Citations
“…If electron neutrinos are detected, the showers that come out of charged current interactions will have a different character depending on y because the neutrino induced electromagnetic (hadronic) shower arising at the leptonic (hadronic) vertex carries a fraction 1 − y (y) of the neutrino energy. In particular it has been recently suggested that it may be possible to measure y by using the radio technique [5]. This tecnique relies of the detection of coherent radio pulses from the excess charge in the induced showers in a dense medium such as ice.…”
Section: Low X Physics and High Energy Neutrino Telescopesmentioning
confidence: 99%
“…The sensitivity to y arises from the elongation of the showers that develop at the electron vertex because of the Landau-Pomerančuck-Migdal (LPM) [24] effect [5].…”
Section: Low X Physics and High Energy Neutrino Telescopesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the spectrum of Cherenkov radiation is approximately the Fourier transform of the distribution of excess negative charge [19,20], we assess the goodness of the thinning algorithms based on their ability to reproduce this distribution, reflected by the parameter set defined in Table 1. Of these, total excess tracklength T is the most useful, since it has very low intrinsic variability, and scales with the primary particle energy.…”
Section: Testing Thinning Methodsmentioning
confidence: 99%
“…Tracking all 10 12 particles expected in a single EeV shower is infeasible with current technology. A parameterisation of the emitted radiation in ice at EeV energies was performed in the past exploiting the analogy with diffraction by a single slit by Fourier-transforming an approximate longitudinal and lateral profile of the shower [18][19][20]. Results for other 2 media were obtained using simple scaling relationships, which at TeV energies and for the regolith differ by ∼30% from the results obtained in full Monte Carlo simulations [16].…”
Section: Introductionmentioning
confidence: 99%